Correlation between the Characteristic Flavour of Youtiao and Trans Fatty Acids Assessed via Gas Chromatography Mass Spectrometry and Partial Least Squares Regression Analyses - Xuelian Yang; Xiangyu Zhang; Jianchun Xie; Dongdong Yang; Chengtao Wang (Journal of Food Quality)
This study aimed to analyse trans fatty acid (TFA) levels and key volatile flavour substances in fried youtiao prepared using five common edible oils and the relationship between TFAs and key volatile flavour substances via partial least squares regression (PLSR) analysis. Total TFA levels were the highest on using rapeseed oil during frying (approximately 1.061 mg/g), probably owing to the high content of unsaturated fatty acids in rapeseed oil and their instability. In total, 22 key flavour substances were detected. Although the flavours differed with different oils, flavour compounds including 3-(methyl sulphide) propionic aldehyde, (E,E)-2,4-sebacedienal, nonaldehyde, and 3-hydroxy-2-butanone contributed to overall flavour. PLSR analysis revealed that C18:2, 9t12t is produced with (E)-2-hexenaldehyde and nonaldehyde. (E,E)-2,4-sebacedienal levels were positively correlated with those of C18:2, 9c12t and C18:2, 9t12c. Most aliphatic aldehydes and pyrazines yield C18:3, 9t12t15c TFAs. These results indicate the characteristic flavour profile of youtiao and promote the preparation of healthy fried food.